Toward Federalism; A Constitutional Solution for Indonesia? - Masnur Marzuki (Universitas Islam Indonesia, 2012)
From the beginning history of modern Indonesia, federalism was mostly considered Dutch political design to preserve the fading power ofcolonial in the country. Most Indonesian viewed federalism as Dutch's political hidden agenda to maintain its influence. Therefore, the challenge was directly responded after the post-transfer of sovereignty and independence movement toward a Unitarian state as it exists today. In contrast, with the fall of the Soeharto's regime, some commentators view federalism as a new formula for tackling multi level crisis encountered. Despite fact that federalism seems to have long road to be adopted in Indonesia, this paper argues that federalism, as a system of government, would become best suited political system for Indonesia particularly in managing diversity and tackfing multi crisis.Keywords: Federalism, Unitarian, State, Diversity and Constitution